2013
DOI: 10.1113/jphysiol.2012.248179
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channels in rat horizontal cells regulate feedback inhibition of photoreceptors through an unconventional GABA‐ and pH‐sensitive mechanism

Abstract: Key points• Inhibitory feedback from horizontal cells to photoreceptors regulates synaptic gain and contributes to centre-surround receptive field formation via mechanisms that are not fully understood.• We show that horizontal cell calcium channels and ionotropic GABA receptors mediate the inhibitory feedback, and that the results of their actions are blocked by strong pH buffering with Hepes.• GABA appears to act not upon the photoreceptor but instead upon the horizontal cell itself.The horizontal cell GABA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
113
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(129 citation statements)
references
References 71 publications
12
113
0
Order By: Relevance
“…f Diagram illustrating three theories for the feedback mechanism of horizontal cell processes on the retinal terminal synapse: GABA, protons (H + is pH) and ephaptic transmission (ΔV; an electrical field effect at close range; Gardner et al 2015; Kramer and Davenport 2015). The involvement of GABA is supported by recent studies (Hirano et al 2016; also Liu et al 2013), but they suggest that GABA from horizontal cell processes activates autoreceptors directly on the horizontal cell processes, probably indirectly mediating the pH-based feedback mechanism (Color figure online)…”
Section: Figmentioning
confidence: 72%
See 1 more Smart Citation
“…f Diagram illustrating three theories for the feedback mechanism of horizontal cell processes on the retinal terminal synapse: GABA, protons (H + is pH) and ephaptic transmission (ΔV; an electrical field effect at close range; Gardner et al 2015; Kramer and Davenport 2015). The involvement of GABA is supported by recent studies (Hirano et al 2016; also Liu et al 2013), but they suggest that GABA from horizontal cell processes activates autoreceptors directly on the horizontal cell processes, probably indirectly mediating the pH-based feedback mechanism (Color figure online)…”
Section: Figmentioning
confidence: 72%
“…And as noted, Hirano et al (2016) show evidence supporting a GABA mechanism. However, this latter mechanism seems to be indirect, with GABA released from horizontal cells and activating autoreceptors on the horizontal cells, possibly driving a pH-based feedback mechanism (Liu et al 2013; Hirano et al 2016); a GABA autoreceptor-based mechanism also might be present in lower vertebrates (Klooster et al 2004; Endeman et al 2012). …”
Section: Vertebrate Photoreceptorsmentioning
confidence: 99%
“…The interpretation of these results was not clear but it has been suggested that iodate-induced damage to the photoreceptors produces a loss of glutamatergic signaling to horizontal cells (HC) which in turn impaired HC inhibitory signaling back onto the rods . Normally, HC depolarization in the dark following glutamatergic signaling results in closure of LTCCs on rods (Babai and Thoreson, 2009;Liu et al, 2013). The purpose of HC inhibitory signaling in bright light is most commonly understood in terms of i) controlling conegenerated synaptic gain and ii) lateral inhibition onto cone cells forming the basis of the center-surround organization of vision (Thoreson and Mangel, 2012;Yang and Wu, 1991).…”
Section: Inhibitory Signaling and Rod Cellsmentioning
confidence: 99%
“…This pathway can also mediate feedforward inhibition by activating GABA receptors on bipolar cell dendrites (Haverkamp et al, 2000). Other feedback pathways are: (i) non-synaptic ‘ephaptic’ route involving the presence of hemichannels (Kamermans and Fahrenfort, 2004; Vroman et al, 2013), (ii) pH changes in the synaptic cleft surrounding photoreceptor terminals (Davenport et al, 2008; Vessey et al, 2005) or (iii) the autaptic action of GABA on horizontal cell GABA receptors (Liu et al, 2013). Much work remains to be carried out to identify the mechanism or mechanisms of horizontal cell action, which may vary across species (e.g.…”
Section: Synapse Structure and Connectivity Of Retinal Neuronsmentioning
confidence: 99%